Synthesis of Carbon from Rice Groats at Various Pyrolysis Temperatures and Its Application for the Recovery of Chromium Wastewater from the Tannery Industry - Wahyu Fajar Winata; Ika Yanti (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
The research on synthesis of carbon from rice groats at various pyrolysis temperatures and its application for the recovery of chromium wastewater from the tannery industry by varying pyrolysis temperatures at 300, 400, and 500 °C. The results of carbon synthesis are analyzed in the form of determination of yield, water content, ash content, and iodine number. The best pyrolysis condition with the quality requirement of carbon is at a pyrolysis temperature of 500 °C with 760 mg.g-1 (iodine number). Adsorption kinetics was also carried out to determine the adsorption kinetics of chromium ions from tannery wastewater. Adsorption kinetics model of chromium wastewater from the tannery industry corresponds to the pseudo-second-order kinetics model with R2 is 0.9857, k2 is 0.0093 g.mg-1.min-1, and qe is 28.5714 mg.g-1.